Risk assessment of slope failure considering the variability in soil properties - Cheng, Hongzhan; Chen, Jian; Chen, Renpeng; Chen, Guoliang; Zhong, Yu (Computers and geotechnics, 2018)
To assess the risk of slope failure, this study employs a rigorous method that is referred to as the random finite difference method (RFDM). The RFDM is capable of considering the spatial variability of soil properties subject to different auto-correlation structures. Comparisons with the collected data are made with respect to two idealized slopes, and a parametric analysis is presented. The results demonstrate that the spatial auto-correlation structures significantly affect the slope failure risk. Depending on the rotated angle, the rotated anisotropy auto-correlation structure shows a dual effect on the reliability of the slope compared to a transverse anisotropy case.